Two models solutions for the Douro Estuary: flood risk assessment and breakwater effects - Iglesias, I. (2019)
Estuarine floods are one of the most harmful and complex extreme events occurring in coastal environments. To predict the associated effects, characterize areas of risk and promote population safety, numerical modelling is essential. This work performs a comparison and a combination of two 2-dimensional depth averaged estuarine models (based on openTELEMAC-MASCARET and Delft3D hydrodynamic software packages), to develop a two-model ensemble approach that will improve forecast robustness when compared to a one-model approach. The ensemble was applied to one of the main Portuguese estuaries, the Douro river estuary, to predict the expected water levels associated with extreme river discharges in the present-day configuration with the new breakwaters. This is a region that is periodically under heavy flooding, which entails economic losses and damage to protected landscape areas and hydraulic structures. Both models accurately simulated water levels and currents for tidal- and flood-dominated validation simulations, with correlation values close to 1, "RMSE" below 15%, small "Bias" and "Skill" coefficient close to 1. The two-model ensemble results revealed that the present-day estuarine mouth configuration will produce harsher effects for the riverine populations in case identical historical river floods take place. This is mainly due to the increase in the area and volume of the estuary?s sand spit related to the construction of the new breakwaters.